The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ympev.2014.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus assessment of phylogenetic relationships in Alytes (Anura, Alytidae)

Abstract: With the advent of large multilocus datasets, molecular systematics is experiencing very rapid progress, but important challenges remain regarding data analysis and interpretation. Midwife toads (genus Alytes) exemplify two of the most widespread problems for accurate phylogenetic reconstruction: discerning the causes of discordance between gene trees, and resolving short internodes produced during rapid, successive splitting events. The three species in subgenus Baleaphryne (A. maurus, A. dickhilleni and A. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…For ND4 and ß-fibint7 amplification conditions were those described in Gonçalves et al (2007). For PPP3CAint4, RPL9int4 and C-myc amplification conditions followed Maia-Carvalho et al (2014b). Purified products of each reaction were sequenced with the ABI Prism BigDye Terminator v3.1 Sequencing Kit protocol on an ABI3130xl DNA analyzer (Applied Biosystems, Foster City, California, USA).…”
Section: Amplification Sequencing and Haplotype Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…For ND4 and ß-fibint7 amplification conditions were those described in Gonçalves et al (2007). For PPP3CAint4, RPL9int4 and C-myc amplification conditions followed Maia-Carvalho et al (2014b). Purified products of each reaction were sequenced with the ABI Prism BigDye Terminator v3.1 Sequencing Kit protocol on an ABI3130xl DNA analyzer (Applied Biosystems, Foster City, California, USA).…”
Section: Amplification Sequencing and Haplotype Determinationmentioning
confidence: 99%
“…Second, Maia-Carvalho et al (2014a) revealed the existence of two well-differentiated groups within A. o. boscai, separated by the Douro River, as suggested by Fonseca et al (2003). Additionally, the recent multilocus assessment of phylogenetic relationships in Alytes by Maia-Carvalho et al (2014b) produced inconclusive results about the relationships between major clades in A. obstetricans and indicated conflict with the current morphology-based subspecific taxonomy.…”
Section: Introductionmentioning
confidence: 99%
“…These local‐scale ecological differences among Hyla and Alytes species were also identified in previous attempts to model their distributions (Arntzen, ) and suggest the existence of niche segregation. The two species pairs have similarly old divergence times (Miocene; see Smith et al ., ; Maia‐Carvalho et al ., ), but the temporal scale of their overlap is markedly different: H. meridionalis is inferred to have entered the Iberian Peninsula in recent times, perhaps even in historical times, via human‐mediated introduction (Recuero et al ., ), whereas A. obstetricans and A. cisternasii have both evolved in situ and coexisted for millions of years (Martínez‐Solano et al ., ; Maia‐Carvalho et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Alytes obstetricans is a highly diversified taxon, comprising four subspecies, being the sister taxa to A. muletensis , A. maurus , and A. dickhilleni , with the last two species being more closely related (Fig. A) (Maia‐Carvalho et al ., ). This reconstruction suggests that the absence of a strict matching between auditory sensitivity for high frequencies and call dominant frequency is a secondary event in the history of the genus.…”
Section: Discussionmentioning
confidence: 97%
“…We aimed to determine whether the tuning of the auditory sensitivity of these anurans has a correspondence with the preferences of males and females for calls of low dominant frequencies within the conspecific ranges reported in the literature. In addition, the current knowledge of the phylogenetic relationships among these taxa (Martínez‐Solano et al ., ; Maia‐Carvalho et al ., ) allows interpretations on evolutionary trends of correspondences between auditory sensitivity and vocal traits. These explorations were carried out using a common set‐up between the three taxa, aiming to provide interpretations on potential interspecific differences in auditory sensitivity devoid of difficulties of comparisons based on two previous independent studies (Mohneke & Schneider, ; Bosch & Wilczynski, ).…”
Section: Introductionmentioning
confidence: 99%